G55(P) Common clinical features in children with dengue shock syndrome in Myanmar: A case series. (27th April 2016) - Ekins, S; Halbert, J; Myint, AA
Abstract : Aims: Dengue fever is a relatively common infection in children in the tropics and subtropics. In 2015 there was a significant outbreak of dengue in Myanmar. The aim of this case series is to identify common clinical features in children presenting with dengue shock syndrome (DSS) in Myanmar. Methods: The medical notes of 26 children presenting with DSS to Mandalay Children's Hospital in Myanmar during the rainy season (September 2015) were reviewed by a single investigator. Demographic and clinical details were recorded in a secure anonymous database. Results: The mean age of the 26 children was 6 years (range 9 months - 12 years). The majority of children presented to hospital after 4–5 days of fever and developed DSS after 5 days of fever. Haemorrhagic symptoms included: haematemesis (42%), malaena (35%), petechiae (12%), gum bleeding (8%), epistaxis (4%), haematuria (4%) and bruising (4%). Other symptoms included: cold clammy extremities (42%), abdominal pain (39%), abdominal distension (27%), respiratory distress (31%), vomiting (19%), loss of appetite (19%), convulsions (19%), irritability (15%), facial puffiness (12%) and restlessness (12%). Typical laboratory investigation findings included lymphocytosis, thrombocytopenia and a microcytic anaemia. Medical treatment included the use of paracetamol, ranitidine, phytonadione, oral rehydration solution, normal-saline, dextrose-saline, gelofusine, fresh whole blood, platelets and furosemide. 4 (15%) of the children died from fluid overload, disseminated intravascular coagulation, gastrointestinal haemorrhage and encephalopathy. The mean duration of shock for the surviving 22 children was 6 h with several having 2–3 recurring episodes of shock before making a full recovery. Conclusion: DSS remains a significant cause of morbidity and mortality in children. Common symptoms included cold clammy extremities, haemorrhage, gastrointestinal symptoms, dyspnoea, and convulsions. Early recognition of dengue warning signs and symptoms with intensive care monitoring and fluid management is key to improving outcome in DSS.